An extended release ciprofloxacin/dexamethasone hydrogel for otitis media. (November 2020) - Ku, Matthew; Cheung, Shirley; Slattery, William; Pierstorff, Erik
Abstract: Objective: Otitis media and associated otorrhea are frequent complications following tympanostomy tube insertion; the most common otologic procedure performed in children in the United States. Current treatments include the administration of antibiotic or antibiotic/anti-inflammatory combination drops to the affected ear. Several studies have demonstrated that using an antibiotic/anti-inflammatory combination product is more effective than the use of antibiotics alone. However, administration of any drops through the tympanostomy tube is very difficult in children, and patient compliance can be an issue. Our group has developed a novel combination drug/hydrogel formulation for the treatment of otitis media/otorrhea that releases both ciprofloxacin and dexamethasone over a 2–3 week period. This has the potential to offer significant advantages over current treatments in use in the clinic. Methods: The release of drugs from the combination hydrogel was validated in vitro over the desired time frame and the activity of the released drugs was monitored via assays to confirm retention of full activity throughout the dissolution period. The safety of the ciprofloxacin/dexamethasone hydrogel and its inactive excipients was evaluated through in vivo otic toxicity studies in guinea pigs, including hearing tests, gross microscopy, and cytocochleogram analysis. Results: Extended release of both drugs was demonstrated in vitro and antibiotic/anti-inflammatory activities were retained. The hydrogel components and its excipients did not cause adverse reactions in animals, demonstrating safety of the hydrogel combination in vivo . Conclusion: The studies presented lay the groundwork for extended release middle ear hydrogel formulations that are capable of safely releasing combinations of active pharmaceutical agents over a desired period of time. This would be more advantageous than therapeutics that are currently used in the clinic for the treatment of otitis media/otorrhea associated with tympanostomy tube insertion.